O casamento, o regime de bens à luz do direito comparado e o novo regime de participação final nos aqüestos - Silva, José Luiz Mônaco da (2006)
I examined in this doctor s degree thesis two aspects of the marriage: 1) the mat-rimonial community of goods according to the compared Law; 2) the community of goods instituted by the Law n. 10.406, dated January 10th, 2002 (Civil Code). The thesis was divided into six chapters. In the first chapter I discourse about the family in general, according to the Brazilian Law, referring to the 1988 Federal Consti-tution, once the current constitutional order protected not only the family deriving from the marriage but also the family deriving from the stable union between a man and a woman. In the second chapter, I examine the community of goods imposed by the Brazil-ian legislation, considering exclusively the institution of marriage. Although it is known that the stable union also proceeds inheritance relations between the spouses, I decided to focus on the studies about the community of goods established by the marriage. Also in the second chapter I emphasized, among other things, the novelty related to the justi-fied or tempered mutability of the community of goods. In favor of the clause 1.639, § 2o, in the New code, the legislation allowed, in request of both spouses, the modification of the community of goods. Later on, I left the third Chapter to study the matrimonial community of goods re-lated to the compared Law. The examination started with the Roman Law, going through German, Italian, Portuguese, Mexican and Spanish Law. Having knowledge about other countries legislation is indispensable. It has been told that Sólon, the great legislator from Athens, would have traveled for ten years to other places not only think-ing about developing business relations, but also thinking about seeking more advanced models of law for his country. Thence the importance of the compared Law study to improve the peoples legislation. I started the fourth chapter discoursing about the new regim of the final participa-tion in the taken possessions instituted by the native legislator. Germany, Austrian, Switzerland, France and Argentina are countries that know the new community of goods which, in 2003, was effectively introduced in Brazil. The peculiarity of this new community of goods is its hybridity, a combination of communitarian and non-communitarian regim. As long as the conjugal society exists, the spouses behave as if they were married under the legal separation of property regim between husband and wife (non-communitarian regim). However once the partnership is finished, the goods acquired in an onerous way, during the marriage, receive communion (communitarian regim). In the last two chapters (fifth and sixth Chapters) I deal, respectively with antinup-tial agreements and civil or business partnerships between the spouses. These are issues that are directly or indirectly related to the matrimonial community of goods. In refer-ence to the sixth Chapter, I give prominence to the clause 977 of the Civil Code that authorized, with some restrictions, the agreement of society between spouses, that, in the past, aroused enthusiastic dogmatic and jurisprudential polemics